Pengaruh Kompetensi dan Disiplin Kerja terhadap Kinerja Pegawai pada Kantor Inspektorat Daerah Provinsi Gorontalo - Siti Nur Aisa Saleh; Sri Yulianty Mozin; Rusli Isa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The purpose of this study is to ascertain and examine the relationship between competence and employee performance at the Gorontalo Province Regional Inspectorate Office, the relationship between competence and employee performance through work discipline as an intervening variable, and the relationship between competence and employee performance at the Gorontalo Province Regional Inspectorate Office. This study uses a quantitative methodology and an explanatory design. The study's population consisted of all 129 employees of the Gorontalo Province's Regional Inspectorate Office, and a sample size of 30 respondents for targeted PLS analysis was established using particular sampling approaches. Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) utilizing SmartPLS 4.1 software was used to analyze the data. According to the findings, employee performance is positively and significantly impacted by competence by 29.9%. Employee performance is positively and significantly impacted by work discipline by 36.5%. Through work discipline, competence has a 23.1% favorable and considerable indirect impact on employee performance. Competence influences work discipline by 40.5%, and the combined variance of performance explained by competence and discipline () is 74.9%. These results suggest that in order to maximize government internal oversight in Gorontalo Province, structural enhancements in auditor competency together with mental reinforcement of work discipline are crucial.